The nature and implications of water scarcity caused by fluvial sedimentation in the Lower Lusitu River Channel, southern Zambia - Muchanga, Manoah; Singubi, Nordoft; Sichingabula, Henry M.; Wankie, Richman; Zulu, Ian (Frontiers in Freshwater Science, 2025)
River sedimentation has emerged as a critical driver of water scarcity in semi-arid regions, yet most studies neglect sediment accumulation on riverbeds. This study investigates the magnitude, economic implications, and community adaptations to fluvial sedimentation in the Lower Lusitu River Channel, southern Zambia. A mixed-methods approach was used, combining geomorphological field sampling with qualitative focus group discussions across a 15 km downstream channel stretch. Sediment depth was measured at 68 points using a Graduated Sediment Depth (GraSeD) rod, spatially analyzed via the ArcMap 10.4 Inverse Weighted Distance interpolation plugin and further analyzed using polynomial regression. A novel participatory suitability rating of river sand and market data was used to estimate the economic value of sediment. Qualitative data were analyzed using thematic analysis. Results indicate that 2.86 million m3 (4.64 million tons) of sand, approximately equating to 68.34% of the original channel depth, occupied the riverbed, drastically limiting surface water flow. We argue that while the river appears dry from July to December, interstitial water persists throughout, supporting basic household and agricultural needs through 56 community-built wells, pools, and sand reservoirs on the riverbed. Socioeconomically privileged households utilize pumps and plastic container–reinforced wells, whereas poorer households rely on labor-intensive manual fetching. Notwithstanding the fact that interstitial water provides an alternative source of water during the water-stressful period from July to early December, health risks to about 20,000 people in 1,073 households with over 30,000 livestock, potential human–livestock conflicts, and inequities in water access are prevalent. Despite these challenges, the sediment's estimated market value of USD 11.2 million, based on a suitability score of 0.652, presents an underexplored economic opportunity. This study provides empirical evidence that sediment acts as both a barrier to water access and a potential economic asset. It challenges the notion of the Lusitu River as a seasonally dry river by demonstrating sustained subsurface hydrological activity through interstitial water. The findings highlight the potential for policy reform to legalize community-built water infrastructure and regulate sustainable sand extraction. Integrating community resilience strategies with sediment management could enhance water security and livelihoods in similar river systems facing sediment-induced water scarcity and stress.